A Framework of Integrated Recyclability Tools For Automobile Design - Sakundarini, Novita (International Journal of Industrial Engineering: Theory, Applications and Practice, 2013)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:Batang; panose-1:2 3 6 0 0 1 1 1 1 1; mso-font-alt:"Arial Unicode MS"; mso-font-charset:129; mso-generic-font-family:auto; mso-font-format:other; mso-font-pitch:fixed; mso-font-signature:0 151388160 16 0 524288 0;} @font-face {font-family:SimSun; panose-1:2 1 6 0 3 1 1 1 1 1; mso-font-alt:"Arial Unicode MS"; mso-font-charset:134; mso-generic-font-family:auto; mso-font-format:other; mso-font-pitch:variable; mso-font-signature:0 135135232 16 0 262144 0;} @font-face {font-family:"Angsana New"; panose-1:2 2 6 3 5 4 5 2 3 4; mso-font-alt:"Arial Unicode MS"; mso-font-charset:222; mso-generic-font-family:roman; mso-font-format:other; mso-font-pitch:variable; mso-font-signature:16777216 0 0 0 65536 0;} @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0;} @font-face {font-family:"\@SimSun"; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-charset:134; mso-generic-font-family:auto; mso-font-format:other; mso-font-pitch:variable; mso-font-signature:0 135135232 16 0 262144 0;} @font-face {font-family:"\@Batang"; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-charset:129; mso-generic-font-family:auto; mso-font-format:other; mso-font-pitch:fixed; mso-font-signature:0 151388160 16 0 524288 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0in; margin-bottom:.0001pt; text-align:justify; text-justify:inter-ideograph; mso-pagination:none; text-autospace:none; word-break:break-all; font-size:10.0pt; mso-bidi-font-size:12.0pt; font-family:Batang; mso-hansi-font-family:"Times New Roman"; mso-bidi-font-family:"Angsana New"; mso-font-kerning:1.0pt; mso-fareast-language:KO;} p.IEEEAbtract, li.IEEEAbtract, div.IEEEAbtract {mso-style-name:"IEEE Abtract"; mso-style-unhide:no; mso-style-next:Normal; margin:0in; margin-bottom:.0001pt; text-align:justify; text-justify:inter-ideograph; mso-pagination:widow-orphan; layout-grid-mode:char; mso-layout-grid-align:none; font-size:9.0pt; mso-bidi-font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:SimSun; mso-ansi-language:EN-GB; mso-fareast-language:EN-GB; font-weight:bold; mso-bidi-font-weight:normal;} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; mso-fareast-font-family:Batang; mso-bidi-font-family:"Angsana New";} @page Section1 {size:8.5in 11.0in; margin:1.0in 1.0in 1.0in 1.0in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> Vehicles, specifically automobile, provide essential need to society and the use is continually increasing. However, there were many problem arise at the end of their life, primarily related to their disposal. Automobile is a very complex product that comprise of thousand components made from various materials that need to be treated. In addition, short supply of natural resources has called out for opportunities to either reuse or recycle components. End of Life Vehicle (ELV) Directive launched by European Union mandated that recyclability rate of automobile must reach 85% by 2015. The aim of this legislation is to minimize the impact of end of life vehicle, contributing to prevention, preservation and improvement of environment quality and energy conservation. Vehicle manufacturers and suppliers requested to include these aspects at earlier stages of the development of new vehicles, in order to facilitate the treatment of vehicles at the time when they reach the end of their life. Therefore, the automobile industry has to establish its voluntary action plan for ELVs, and has numerical target to improve ELV recycling rate, reduce automotive shredder residue (ASR) landfill volume, and reduce lead content. Many innovative approaches in improving recyclability have been implemented, but still called out for more intelligent solutions which integrate recyclability evaluation in product development stage. This paper attempts to review some of current innovative approach that used to improve recyclability and introduce a framework for integrated recyclability tool to improve product recyclability throughout its development phase.